B. R. Ambedkar: man and his vision - Yadav, Rajkumar (New Delhi Sonali, 2021)
dr. Ambedkar being the first mass-leader of dalit movement formed the basis of a big political movement in modern India.The person is known as ' messiah of outcastes' Dr. Ambedkar's endeavours and work of upliftment of dalits and other weaker section of the societyand as architect of Indian constituion. The bok is highlightened his work for strengthening nationalism in India.
Keywords: Social Sector; Social Group; society; Dalits Movement